PENGARUH LOAN TO DEPOSIT DAN NON PERFORMING LOAN TERHADAP RETURN ON EQUITY PADA PERUSAHAAN SUB SEKTOR PERBANKAN TAHUN 2015-2019 - Dolly Parlindungan Pardosi; Leo Hutagalung (Program Studi Magister Manajemen Universitas Advent Indonesia, 2021)
The company's ability to make a profit is one of the main goals for the company to grow. This research was conducted to see the effect of loan to deposit and non-performing loan on return on equity. The sample of this research is BUMN and BUMD banks which are listed on the Indonesian stock exchange. Determination of the sample using a purposive sample and there are six banks that meet the criteria. The research instrument is the 2015-2019 financial statements. The result of this research is that there is an influence between loan to deposit on return on equity. Likewise, non-performing loans have a negative effect on return on equity. However, simultaneously, loan to deposit and non-performing loan have no effect on return on equity.